Outcome of oncoplastic breast-conserving surgery following bracketing wire localization for large breast cancer. Issue 4 (August 2015) - Malhaire, Caroline; Hequet, Delphine; Falcou, Marie-Christine; Feron, Jean-Guillaume; Tardivon, Anne; Leduey, Alexandre; Guillot, Eugénie; Mosseri, Véronique; Rouzier, Roman; Couturaud, Benoit; Reyal, Fabien
Abstract Purpose The purpose of this study was to evaluate the outcome of breast conserving surgery comparing oncoplastic surgery (OS) and standard lumpectomy (SL) after preoperative bracketing wire localization of large neoplastic lesions. Methods We retrospectively reviewed the medical records and the mammograms of patients operated on at the Institut Curie between May 2005 and September 2011 after bracketing wire localization under mammographic and/or sonographic guidance. Results 113 patients underwent surgery for a pre-operative diagnosis of DCIS (n = 80), micro-invasive carcinoma (n = 9) or invasive carcinoma (n = 24), by OS (n = 73) or SL (n = 40). In the OS group, radiological size (52 mm vs 39 mm, p < 0.001) and resection volumes (246 cc vs 88 cc, p < 0.00001) were significantly higher than in the SL group. Rates of clear histologic margins (60 vs 62%, NS), complete excision of microcalcifications (78% vs 72%, NS) and re-intervention rate (40% vs 42%, NS) were equivalent. The rate of local recurrence at 24 months was 3% [0–7.1] in patients with conservative treatment (n = 3). With a median follow-up of 40 months, 5 local relapses (two with axillary metastatic involvement), two distant metastatic evolution, one contralateral breast cancer and one death unrelated to cancer occurred. Conclusion Following bracketing wire localization, OS allowed the conserving management of significantly larger lesions with wider resection volumes, without significant increase in margin involvement or re-intervention rate, and equivalent rate of microcalcifications clearance compared to SL.